Strengthening Polri Law Enforcement through Digital Identification Systems to Realize Domestic Security Stability (KAMDAGRI) - Arifiya Zaen, Wido Dwi; Setiono, Joko; Prisgunanto, Ilham (Greenation Publisher & Yayasan Global Resarch National, 2025)
Digital transformation is an integral part of the modernization of law enforcement institutions, including Polri, in maintaining domestic security stability (Kamdagri). The utilization of digital technologies such as the Automated Biometric Identification System (ABIS), face recognition, and integration of population data are strategic steps taken by Polri to increase the effectiveness of law enforcement. This study uses a normative juridical method by reviewing relevant legislation, such as Law Number 2 of 2002 on the Indonesian National Police, Law Number 27 of 2022 on Personal Data Protection, and Minister of Communication and Informatics Regulation Number 5 of 2020 on the Implementation of Electronic Systems in the Private Sector. The study’s findings show that digital identification systems can enhance the efficiency of crime detection and handling but pose serious legal challenges, such as privacy protection, system accuracy, and potential data misuse. There is a need for a more specific and updated internal legal basis within Polri to regulate the governance of these digital technologies. This journal proposes integrating the principles of transparency, accountability, and human rights protection at every stage of implementing identification technology to ensure synergy between security interests and the protection of civil right.